University students’ rankings and reflections on technologies value to their learning - Whittier, David B. (Série-Estudos, 2015)
The Measuring Technologies Value to Learning (MTVL) survey instrument was developed and deployed to collect data on the value learners place on 37 specific technologies and in some cases, the processes they facilitate. Administered to university students in three different locations in the spring of 2014, findings provide evidence to educators on the value to learning of measured items. Surprisingly, “writing with a word processor” was rated number one for its value to learning (n=386). The constructivist and didactic deployment of technologies was also surveyed for their value to learning. Constructivist usages with technology ranked four of the top five and didactic learning from technology occupied four out of the top ten and eight of the top 15 value rated positions, indicating value of both types of use. Respondents indicated a high degree of meta-awareness of technologies value to learning and a higher degree of ability to communicate and collaborate in-person compared to through social networking or any other online tools. Findings support the pedagogical use of technologies and show relative value of different tools. Key words: Technology. Value. Learning.